Paguyuban sebagai Media Transformasi Sosial-ekonomi Keluarga Perempuan TKI Purna Penempatan? Sebuah Perspektif Antropologi Migrasi - Setiadi Setiadi (Populasi, 2020)
The Phenomenon of Feminization of Indonesian Workers has placed women in strategic positions in the family. One reason is the number of economic and social remittances they have. The great number of remittances requires the optimization of the utilization of remittances through economic and social entrepreneurship. The success of strengthening this Retiring Female Indonesian Workers is a strategic matter. In the long run, there will be an increase in the quality of life of the Indonesian workers’ households. However, this study proves that Remitan and the social (network) of retiring women do not necessarily increase or strengthen their economic roles. The articulation of the roles and position of retiring female Indonesian workers (migrants) in the family and community in developing businesses (social and economic entrepreneurship) lacks significant influence. Why has the entrepreneurship of retiring female workers failed to be achieved? This study with the anthropological approach to migration proves that there are three important factors that influence it, i.e.the low capacity of female migrants to using the accumulation of income while working abroad and the internal conditions of family gender relations, and the low facilitation capacity of institutions/agencies for social change towards migrant families.